Actin cytoskeleton regulates functional anchorage-migration switch during T-cadherin-induced phenotype modulation of vascular smooth muscle cells. Issue 1 (2nd January 2018) - Frismantiene, Agne; Kyriakakis, Emmanouil; Dasen, Boris; Erne, Paul; Resink, Therese J.; Philippova, Maria
ABSTRACT: Vascular smooth muscle cell (SMC) switching between differentiated and dedifferentiated phenotypes is reversible and accompanied by morphological and functional alterations that require reconfiguration of cell-cell and cell-matrix adhesion networks. Studies attempting to explore changes in overall composition of the adhesion nexus during SMC phenotype transition are lacking. We have previously demonstrated that T-cadherin knockdown enforces SMC differentiation, whereas T-cadherin upregulation promotes SMC dedifferentiation. This study used human aortic SMCs ectopically modified with respect to T-cadherin expression to characterize phenotype-associated cell-matrix adhesion molecule expression, focal adhesions configuration and migration modes. Compared with dedifferentiated/migratory SMCs (expressing T-cadherin), the differentiated/contractile SMCs (T-cadherin-deficient) exhibited increased adhesion to several extracellular matrix substrata, decreased expression of several integrins, matrix metalloproteinases and collagens, and also distinct focal adhesion, adherens junction and intracellular tension network configurations. Differentiated and dedifferentiated phenotypes displayed distinct migrational velocity and directional persistence. The restricted migration efficiency of the differentiated phenotype was fully overcome by reducing actin polymerization with ROCK inhibitor Y-27632 whereas myosin II inhibitor blebbistatin was less effective. Migration efficiency of the dedifferentiated phenotype was diminished by promoting actin polymerization with lysophosphatidic acid. These findings held true in both 2D-monolayer and 3D-spheroid migration models. Thus, our data suggest that despite global differences in the cell adhesion nexus of the differentiated and dedifferentiated phenotypes, structural actin cytoskeleton characteristics per se play a crucial role in permissive regulation of cell-matrix adhesive interactions and cell migration behavior during T-cadherin-induced SMC phenotype transition.